Underlätta resiliens och öka delaktighet för personer med fibromyalgi - En kartläggning av arbetsterapeutiska interventioner och dess effekt - Lorentzen,Maja; Jönsson,Moa (2025)
Background: Fibromyalgia is a controversial chronic disease with the cardinal symptoms of pain and fatigue. These symptoms affect everyday life and result in people with fibromyalgia needing to make changes in their activity patterns. Aim: To chart occupational therapy interventions, their content, effect and perceived experience of the participants, which aim to facilitate resilience and increase occupational participation for people with fibromyalgia. Method: Literature study with integrative content analysis and inductive approach. The study included original articles with qualitative, quantitative and mixed methods. The articles only needed to have an indirect connection to the concepts of resilience or occupational participation. Result: The twelve selected articles showed that the variation of occupational therapy interventions was large. The content analysis resulted in an overall theme, energy management in everyday life. The first main category was activity adaptation with the subcategories managing pain and fatigue and improving ADL ability and ergonomics. The second main category was activity engagement with the subcategories enabling self-selected meaningful activities and improving social participation in groups. Conclusion: Good energy management can contribute to satisfaction in ADL ability and activity engagement. Occupational therapy interventions for people with fibromyalgia involve energy management through activity adaptation, strategies for pain and fatigue, promoting meaningful activities and socially inclusive activities, which facilitates resilience and increases a sense of occupational participation. Group interventions had particularly positive effects on motivation and social support. Occupational therapists have an important role in the team for people with fibromyalgia.
Keywords: Fibromyalgi; kronisk smärta; fatigue; resiliens; delaktighet i aktivitet; arbetsterapeutisk intervention